Impact response of balsa core sandwiches (Fracture and Structural Integrity, 2014)
The benefits of resins nano-enhanced on the impact response of sandwich composites made by fiber glass/epoxy skins and balsa wood core were studied. Afterwards, the influence of the core's discontinuity was analyzed in terms of impact strength. For better dispersion and interface adhesion matrix/clay nanoclays were previously subjected to a silane treatment appropriate to the epoxy resin. Resins enhanced by nanoclays promote higher maximum impact loads, lower displacements and the best performance in terms of elastic recuperation. The core's discontinuity decreases the impact strength, but the resin enhanced by nanoclays promotes significant benefits.
Keywords: Sandwich composites